Pengaruh Media Pembelajaran Digital dalam Meningkatkan Keterampilan Literasi Anak Usia 5-6 Tahun - Nazara, Dewi Kurnia; Noviana Mustapa; Hendriawan, Deri; Mahabbati, Aini (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Literacy development in children aged 5–6 is crucial for fostering cognitive growth, school readiness, and social competence. However, implementing effective literacy teaching strategies remains challenging in diverse educational settings. This study employs a Systematic Literature Review (SLR) to examine the impact of digital learning media on early childhood literacy, focusing on the competencies developed and factors influencing effectiveness. Analysis of 34 selected studies reveals that digital media significantly enhances literacy skills, particularly in language, communication, and cognitive domains. Interactive tools such as digital storybooks, educational applications, and learning games promote engagement, vocabulary expansion, narrative comprehension, and critical thinking. The active involvement of parents and educators is essential in guiding children and selecting developmentally appropriate digital content. Although the direct effects on reading and writing acquisition remain underexplored, findings suggest that integrating digital media in literacy instruction can make learning more enjoyable and effective. The study concludes that digital media serves as a promising pedagogical tool to strengthen early literacy when supported by active adult participation, thoughtful content design, and conducive learning environments.